Effect of dietary modified zeolite (clinoptilolite) on growth performance of gilthead sea bream (Sparus aurata) in the recirculating aquaculture system. (13th November 2021) - Kaya, Dogukan; Genc, Ercument; Palić, Dušan; Genc, Münevver Ayce; Todorović, Nemanja; Sevgili, Huseyin; Vasiljević, Marko; Kanyılmaz, Mahir; Guroy, Derya
Abstract: In this study, the effects of six different dietary levels of commercial surface‐modified clinoptilolite (Minazel Plus ® [MP]; 0, 1, 1.5, 2, 2.5 and 3 g kg −1 ) were observed for fingerling gilthead sea bream in recirculating aquaculture system (RAS) for 60 days. All experimental groups showed higher final weight, weight gain and specific growth rate compared with the control group, with 2 g kg −1  MP showing the highest levels ( p  < 0.05). Feed conversion ratio was lower than the control group in all MP‐supplemented groups ( p  < 0.05). No significant effects on survival rates were detected among the groups. Body indices as viscerosomatic index and hepatosomatic index and blood parameters (haematocrit, haemoglobin, white blood cell and red blood cell, glucose and alanine aminotransferase and aspartate aminotransferase enzymes) were not significantly different among the groups. The addition of zeolite in feed did not show any differences in whole‐body protein and fat levels. Therefore, feed supplementation with 2 g kg −1 surface‐modified clinoptilolite has been evaluated as safe and supportive of general health and growth parameters in the culture of Sparus aurata in the RAS.